Pengaruh Pengembangan Karir, Kompetensi dan Kecerdasan Emosional Terhadap Kinerja Pegawai BKPSDM Kabupaten Ponorogo - Vika Ervianti; Umi Farida; Wahna Widhianingrum (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the influence of career development, competence, and emotional intelligence on employee performance at the BKPSDM of Ponorogo Regency. This study uses a quantitative approach with data collection through questionnaires, with a population of 50 employees being sampled using a saturated sampling technique. Data analysis was carried out using multiple linear regression analysis with the help of SPSS and supported by validity tests, reliability tests, t-tests, and f-tests. The results of the study indicate that partially and simultaneously the variables of career development, competence, and emotional intelligence have a significant effect on employee performance. The coefficient of determination value of 86.3% indicates that most of the influence of employee performance can be explained by these three variables, while the rest is influenced by other factors outside the study. These findings indicate that improving employee performance can be optimized through targeted career development management, increasing competence, and strengthening emotional intelligence on an ongoing basis.